The Use of Authentic Materials In â€œCambridge Primary English Stage 4 Learner’s Bookâ€ to Teach Reading (A Case Study) - Purwaningrum, Endah Aprilia (Universitas Alma Ata, 2019)
This research aimed at: (1) identifying the authentic materials written in â€œCambridge Primary English Stage 4 Learner’s Bookâ€; (2) describing how authentic materials are implemented to teach reading; and (3) describing the problems in implementing authentic materials to teach reading and solutions proposed by the teacher. This research was designed as qualitative case study conducted in Islamic International Private Elementary School in Surakarta. The subject of the research was the English teacher who each reading at the fourth grade of international class program (ICP). The research data were collected through observation, interview, teaching learning documents, textbook analysis and were analyzed by using interactive model proposed by Miles, Hubarman, and Saldana (2014). Findings of the research were: (1) the authentic materials used in â€œCambridge Primary English Stage 4 Learner’s Bookâ€ were: a) posters, b) book covers, c) cards, d) book index, and e) blurb. (2) The implementation of the use of authentic materials in â€œCambridge Primary English Stage 4 Learner’s Bookâ€ were: a) posters were used to inform the students the elements of the narrative text or story, b) book covers were used to analyse and guess the content of book or story which is included title, character, setting, plot, and mood based on its covers, c) cards were used by to teach descriptive text, d) book index was used to teach ordered information and e) blurb was used to teach how to identify the content of the story book. Most of the authentic materials were used in pre-reading activities. (3) Five problems in implementing authentic materials to teach reading were: a) the students’ understanding of English grammar, b) the content of authentic material, c) comprehensive linguistic competences to write correct sentence was less related to grammar function, d) language focus related the text which the students was going to write, and e) students’ lack of vocabulary mastery. Four Solutions proposed by the teacher were (a) giving new vocabulary and stimulation words, (b) studying the other example of authentic material related to the material discussed, (c) having discussion with students, and (d) improving students’ understanding about the discussed materials. It is recommended to use textbook entitled â€œCambridge English Primary Stage 4 Learner’s Bookâ€ not only in the school where the researcher conducted the research, but also in other elementary schools emphasing on teaching reading skill by using authentic materials. Keywords: Authentic Material, Cambridge English Textbook, Reading Skill.